ANALISIS RISIKO USAHATANI BUNGA KRISAN POTONG (Chrysanthenum indicum L) (Studi kasus di PT Alam Indah Bunga Nusantara) - Jannet Aszury Astaningrum; Endah Djuwendah (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2015)
Horticulture is one of the sub-sectors in agriculture that have the potential to be developed asit has a high economic value. One of the featured plants that have good prospects for development in Indonesia is the chrysanthemum. In the process of cultivation of chrysanthemums, required skills and intensive treatment of the chrysanthemum. therefore at high risk of cultivation process. PT Alam Indah Bunga Nusantara is one of the companies engaged in the agribusiness plants located in West Java. The purpose of this research was to determine factors that will influence the risk in chrysanthemum cut flower farm, to determine the extent of risk management which conducted in PT Alam Indah Bunga Nusantara, and know the strategies to improve risk conducted in PT Alam Indah Bunga Nusantara. The study design used was a qualitative design using FMEA analysis (Failure Mode and Effect Analysis). Engineering research is tostudy the case. The result was the risks faced in PT Alam Indah Bunga Nusantara is the weather and the climate change problem that occurs is uncertain. In addition, pests and diseases is also a risk that must be covered by the company. This can lead to a lot of things that could detrimental to the company in the business of chrysanthemums. In addition to natural factors, uncertainty in consumer tastes is a cause of risk faced by PT Alam Indah Bunga Nusantara. The new effort conducted by PT Alam Indah Bunga Nusantara in improving the quality of human resources in the company is to conduct junior secondary education program. The strategy must do for PT Alam Indah Bunga Nusantara for improve the risk is repair the greenhouse to be more optimized than previous, adding a thermostat in the greenhouse.